Pengaruh Belanja Daerah dan Indeks Pembangunan Manusia terhadap Pertumbuhan Ekonomi di Provinsi Aceh (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the effect of Regional Expenditure and the Human Development Index on Economic Growth in Aceh Province. The research method used is quantitative, and the data will be analyzed according to the required model. Data processing was carried out using multiple linear regression with the Eviews10 software. The data source used is secondary data obtained from historical records available in published archives. The findings of the study reveal that Regional Expenditure has a positive but insignificant effect on Non-Oil and Gas Economic Growth in Aceh Province, while the Human Development Index also shows a positive but insignificant effect on Non-Oil and Gas Economic Growth in Aceh Province. Simultaneously, both variables do not have a significant effect on Non-Oil and Gas Economic Growth in Aceh Province. Based on the regression analysis, the R-squared (R²) value was recorded at 0.2166. This indicates that Regional Expenditure and the Human Development Index can explain 21.66% of the variation in Non-Oil and Gas Economic Growth in Aceh Province, while the remaining 78.34% is influenced by other variables not included in this research model, such as investment, unemployment rate, inflation, taxes, subsidies, export-import, international trade, exchange rates, and household consumption.